Wood extraction in the Brazilian caatinga region and the risks to rural workers - Fernandes, Cristina da Silva; Sousa, Vitória Lídia Pereira; Oliveira, Francisco Eduardo Silva de; Rosemiro , Francisco Rosemiro Guimarães Ximenes Neto; Santos, Francisco Diogenes dos; Lourenção, Luciano Garcia; Machado, Maria Helena; Oliveira, Eliany Nazaré; Sousa, Francisco Willian Melo de (Población y Salud en Mesoamérica, 2024)
Objective: To describe the work process of rural workers during logging and the occupational risks involved. Method: A qualitative, descriptive-exploratory study carried out in the municipality of Cariré, Ceará, with 10 rural workers. Data was collected through semi-structured interviews and direct observation. The analysis was based on Minayo's theoretical framework. Results: The work of the extractivists involves selecting sites for camping, after leasing land; building roads to transport timber, extracting, transporting and burning waste. These workers, who have no formal employment relationship, face substandard working conditions and are exposed to various risks, such as excessive solar radiation, handling sharp tools, exposure to smoke, bites from venomous animals, and intense physical effort, without the proper use of Personal Protective Equipment. Conclusion: The study highlights the urgent need for public health policies that guarantee comprehensive and universal protection for rural workers, with a view to reducing occupational risks and improving working conditions.